2012
DOI: 10.4274/jcrpe.787
|View full text |Cite
|
Sign up to set email alerts
|

Hypochondroplasia in a Child With 1620c>G (Asn540lys) Mutation in FGFR3

Abstract: Hypochondroplasia (HCP) is an autosomal dominant skeletal dysplasia characterized by short extremities, short stature and lumbar lordosis, usually exhibiting a phenotype similar to but milder than achondroplasia (ACP). Fibroblast growth factor receptor 3 gene (FGFR3) mutations in the germline are well-known causes of skeletal syndromes. FGFR3 is a negative regulator of bone growth and all mutations in FGFR3 are gain-of-function mutations that lead to skeletal dysplasias. We report a child who presented with sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…[21] Some studies showed that individuals with the FGFR3 N540K mutation may have an increased incidence of mild to moderate intellectual disability or learning disabilities. [42] However, Song et al (1999) suggested that the clinical findings were similar in 2 groups of HCH with or without FGFR3 mutations, only the radiological findings of mesomelia of upper and lower limbs and, L1/L4 ratio in anterior–posterior and lateral view were more typical in HCH with FGFR3 mutations than in HCH without FGFR3 mutations. [8] De Rosa et al described a 16-month-old male with N540K homozygous mutation in the FGFR3 gene who showed a more severe phenotype than the usual heterozygous HCH, which was even shorter than the heterozygous ACH.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Some studies showed that individuals with the FGFR3 N540K mutation may have an increased incidence of mild to moderate intellectual disability or learning disabilities. [42] However, Song et al (1999) suggested that the clinical findings were similar in 2 groups of HCH with or without FGFR3 mutations, only the radiological findings of mesomelia of upper and lower limbs and, L1/L4 ratio in anterior–posterior and lateral view were more typical in HCH with FGFR3 mutations than in HCH without FGFR3 mutations. [8] De Rosa et al described a 16-month-old male with N540K homozygous mutation in the FGFR3 gene who showed a more severe phenotype than the usual heterozygous HCH, which was even shorter than the heterozygous ACH.…”
Section: Discussionmentioning
confidence: 99%
“…Arm span is an important measure in the assessment of short-limbed short stature (or long-limbed high height) resulting from growth hormone deficiency, chromosomal disorders (Turner syndrome, Marfan syndrome, etc.) and skeletal dysplasia (achondroplasia, hypochondroplasia, rickets and so on) in children [ 1 4 ]. In an epidemiological survey, with a large number of subjects’ indicators, it is especially valuable to establish methods which can measure both quickly and accurately.…”
Section: Introductionmentioning
confidence: 99%